Quantitative measurement of heat transfer fluctuation in a pipe flow around an orifice plate using high-speed infrared thermography - Naoki SHIIBARA; Hajime NAKAMURA; Shunsuke YAMADA (Mechanical Engineering Journal, 2015)
The aim of the present study is to demonstrate the quantitative measurement of the spatio-temporal fluctuation of the heat transfer in a water pipe flow around an orifice plate. In the present study, a technique using high-speed infrared thermography was used to measure the heat transfer. The measurement was first performed for a fully developed pipe flow without installing an orifice plate in order to verify the validity of the measurement technique. The spatio-temporal distribution of the heat transfer coefficient was evaluated based on the temperature fluctuation of a heated thin-foil measured using high-speed infrared thermography, and the results indicated that quantitative measurement was possible not only for time-averaged values, but also for fluctuating values. The technique was then used to measure the heat transfer to the flow around an orifice plate (the bore ratio was approximately 0.5). As a result, it was revealed that the heat transfer downstream of the orifice fluctuated violently, and the instantaneous structure of the heat transfer was remarkably finer than the streaky structure for the fully developed pipe flow. The time-averaged value of the heat transfer had a maximum at approximately two diameters downstream of the orifice, where the rms value of the fluctuation and its characteristic frequency also became much higher than those for the fully developed pipe flow.